Biological embedding of neighborhood disadvantage and collective efficacy: Influences on chronic illness via accelerated cardiometabolic age. (14th August 2018) - Lei, Man-Kit; Beach, Steven R. H.; Simons, Ronald L.
Abstract: The present study extends prior research on the link between neighborhood disadvantage and chronic illness by testing an integrated model in which neighborhood characteristics exert effects on health conditions through accelerated cardiometabolic aging. Hypotheses were tested using a sample of 408 African Americans from the Family and Community Health Study. Using four waves of data spanning young adulthood (ages 18–29), we first found durable effects of neighborhood disadvantage on accelerated cardiometabolic aging and chronic illness. Then, we used marginal structural modeling to adjust for potential neighborhood selection effects. As expected, accelerated cardiometabolic aging was the biopsychosocial mechanism that mediated much of the association between neighborhood disadvantage and chronic illness. This finding provides additional support for the view that neighborhood disadvantage can influence morbidity and mortality by creating social contexts that becomes biologically embedded. Perceived neighborhood collective efficacy served to buffer the relationship between neighborhood disadvantage and biological aging, identifying neighborhood-level resilience factor. Overall, our results indicate that neighborhood context serves as a fundamental cause of weathering and accelerated biological aging. Residing in a disadvantaged neighborhood increases biological wear and tear that ultimately leads to onset of chronic illness, but access to perceived collective efficacy buffers the impact of these neighborhood effects. From an intervention standpoint, identifying such an integrated model may help inform future health-promoting interventions.